The Dynamics of the Middle Class in Russia in 1990s - Алина Игоревна Трусова (Journal of Economic Sociology, 2010)
The paper is based on the assumption that Russian society has at least two middle classes at the same time. Using three criteria of the middle class identification (material position, professional qualification factor and self positioning) the author identifies the “core” (social group, having the basic indications of the middle class) and “proto-middle classes” (those who have one or several main indications) and analyzes their mobility then. The part of paper is devoted to the empirical study of the dynamics of the middle class and the analysis of the mobility of the chosen criteria. The study is based of the RLMS for 1995-1998. It was shown that the number of the main body of the middle class changed during the considered period not more than 10%, while its structure changed for 62% on average during the year. The same situation was disclosed for the proto-middle classes. As the result the author refuted the hypothesis of the stable core of the middle class